Survival of Curtobacterium flaccumfaciens pv. flaccumfaciens in soil and bean crop debris - Silva, T. A.F. [UNESP]; Negrão, D. R. [UNESP]; Itako, A. T. [UNESP]; Soman, J. M. [UNESP]; Maringoni, A. C. [UNESP] (My University, 2012)
The survival of Curtobacterium flaccumfaciens pv. flaccumfaciens was evaluated as free cells in the soil, under laboratory conditions, and on infected bean residues retained on the soil surface or buried 20 cm deep, in 2008 and 2009. Free bacterial cells survived in the soil between two and 16 days. Survival was influenced by soil type, moisture and incubation temperature of the samples. In field tests, climatic conditions and incorporation of infected crop residues influenced bacterial survival the most. C. flaccumfaciens pv. flaccumfaciens survived up to 240 days on bean residues retained on the soil surface, but 30 days only when these were incorporated 20 cm deep into the soil. Because C. flaccumfaciens pv. flaccumfaciens-infected bean debris can be an important source of inoculum, soil incorporation of crop residues and rotation using non host crops for the pathogen are recommended to prevent disease epidemics.
Keywords: Bacteria; Bean bacterial wilt; Epidemiology; Phaseolus vulgaris